The Effect of Compession and Discipline on Employee Performance at P.T. Indolacto - Rachmawati, Rizki; Sugiarti, Sri; Simanulang, Fransiska; Simanulang, Sairun (Formosa Journal of Sustainable Research, 2025)
Employee compensation and discipline can influence employee performance in the company, so human resource management must pay attention to this if they want to improve employee performance. The problem formulation is the influence of compensation and discipline on employee performance. Data processing is assisted by tools, namely SPSS V.24. The results of data processing obtained a correlation coefficient of 0.878, this shows that the influence is very strong, if seen from the coefficient of determination, namely 0.762 (76.2%) it means that the influence is 76.2%, while the last 23.8% is influenced by additional elements not examined in the F test, resulting in a calculated F of 87.452, while the F table of 3.16 shows that if the calculated F is greater than the F table (87.452 is greater than 3.16), then Ho is rejected and Ha is accepted, indicating that compensation and discipline influence the performance of P.T. employees. Indolacto